104k views
3 votes
Find (f + g)(x), if f(x) = - 5x2 + 6 and g(x) = x2 - 6.4x2- 6x2 + 12- 4x2- 6x2 - 12

Find (f + g)(x), if f(x) = - 5x2 + 6 and g(x) = x2 - 6.4x2- 6x2 + 12- 4x2- 6x2 - 12-example-1
User Vanetta
by
4.9k points

1 Answer

4 votes

Given the functions:


\begin{gathered} f(x)=-5x^2+6 \\ g(x)=x^2-6 \end{gathered}
\begin{gathered} (f+g)(x)=f(x)+g(x) \\ (f+g)(x)=(-5x^2+6)+(x^2-6)=-5x^2+x^2+6-6 \\ (f+g)(x)=-4x^2+0=-4x^2 \end{gathered}

The answer is: C. -4x^2.

User Dumamilk
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.